Regulated Assembly of the V-ATPase: Structural Insights, Physiological Function, and Control by Cellular Signaling Pathways. - Liberman, Rachel. (2017)
Abstract: The vacuolar (H+)-ATPases (V-ATPases) are ATP-driven proton pumps composed of a peripheral V1 domain and a membrane embedded V0 domain. Regulated assembly of V1 and V0 represents an important regulatory mechanism for controlling V-ATPase activity in vivo. This thesis investigates regulated assembly using both yeast as a model system and dendritic cells, where V-ATPase activity is important for antigen processing. In yeast, regulated assembly was investigated both structurally and by investigating cellular signaling pathways which modulate assembly. Subunit a is a 100 kDa membrane protein that possesses an N-terminal cytoplasmic domain and a C-terminal hydrophobic domain. The N-terminal domain is critical for intracellular targeting and regulation of V-ATPase assembly. Despite its importance, there is currently no high resolution structure for subunit a of the V-ATPase. We have used homology modeling to construct a model of the N-terminal domain of Vph1p, one of two isoforms of subunit a expressed in yeast. The results of studies investigating accessibility of introduced cysteine residues to chemical modification provide an experimental test of the proposed model and have identified regions of the N-terminal domain of subunit a that likely serve as interfacial contact sites with the peripheral V1 domain. Regulated assembly of the V-ATPase in yeast is mediated by the Ras/cAMP/PKA pathway, and we tested the hypothesis that PKA-dependent phosphorylation of the V-ATPase subunit C functions in this regulation. Site-directed mutagenesis of consensus PKA phosphorylation sites in subunit C was performed. The resulting mutant displayed normal assembly and glucose-dependent disassembly, indicating that none of the PKA consensus sites on subunit C are required for glucose-dependent regulation of V-ATPase assembly. Future plans to identify downstream mediators of PKA, or the direct phosphorylation of other pump subunits, is discussed. Dendritic cells function in antigen processing as part of the adaptive immune response. In dendritic cells, cluster disruption induces a semi-mature phenotype associated with immune tolerance. Thus, semi-mature dendritic cells are able to process and present self-peptides to suppress autoimmune responses. We have investigated V-ATPase assembly in bone marrow-derived, murine dendritic cells, and have observed an increase in assembly and activity following cluster disruption. This increased assembly is not dependent upon new protein synthesis and is regulated by a PI 3-kinase/mTOR dependent pathway. The significance of this finding for the treatment of autoimmune diseases is discussed.; Thesis (Ph.D.)--Tufts University, 2014.; Submitted to the Dept. of Cellular & Molecular Physiology.; Advisor: Michael Forgac.; Committee: Laura Liscum, Peter Juo, Alexander Poltorak, Brent Cochran, and Sylvie Breton.; Keywords: Physiology, and Biochemistry.